Plant-derived bioactive compounds regulate the NLRP3 inflammasome to treat NAFLD - Huang, Qian; Xin, Xin; Sun, QinMei; An, Ziming; Gou, Xiaojun; Feng, Qin (Frontiers in Pharmacology, 2022)
Non-alcoholic fatty liver disease (NAFLD) is a liver disorder characterized by abnormal accumulation of hepatic fat and inflammatory response with complex pathogenesis. Over activation of the pyrin domain-containing protein 3 (NLRP3) inflammasome triggers the secretion of interleukin (IL)-1β and IL-18, induces pyroptosis, and promotes the release of a large number of pro-inflammatory proteins. All of which contribute to the development of NAFLD. There is a great deal of evidence indicating that plant-derived active ingredients are effective and safe for NAFLD management. This review aims to summarize the research progress of 31 active plant-derived components (terpenoids, flavonoids, alkaloids, and phenols) that alleviate lipid deposition, inflammation, and pyroptosis by acting on the NLRP3 inflammasome studied in both in vitro and in vivo NAFLD models. These studies confirmed that the NLRP3 inflammasome and its related genes play a key role in NAFLD amelioration, providing a starting point for further study on the correlation of plant-derived compounds treatment with the NLRP3 inflammasome and NAFLD.